Quality of Life in Iranian Breast Cancer Patients Undergoing Chemotherapy: A Cross-Sectional Study from Qazvin - Alijaniha, Mahfam; Mirzaalimohammadi, Mahdi; Alijaniha, Mahdin (Asian Pacific Journal of Cancer Care, 2025)
Background and Aims: Breast cancer is a leading health concern among Iranian women. This study evaluated the quality of life (QoL) in breast cancer patients undergoing chemotherapy at a specialized cancer center in Qazvin, Iran. Materials and Methods: This cross-sectional study included 50 women aged ≥18 years with breast cancer receiving chemotherapy from the second cycle onward. Participants completed validated Persian versions of EORTC QLQ-C30 and QLQ-BR23 questionnaires. Cognitive function was assessed using a standardized cognitive assessment battery. Results: Emotional functioning was the most severely affected QoL domain. Cognitive impairments were observed in working memory (25.3), reaction time (21.1), and organizational skills (22.1). Prevalent symptoms included insomnia (13.5), fatigue (12.4), and appetite loss (11.6). Significant negative correlations were found between psychological symptoms and overall QoL (p<0.05). Conclusion: Chemotherapy significantly impacts multiple QoL dimensions in Iranian breast cancer patients. Integrated interventions addressing cognitive rehabilitation and psychological support are essential components of comprehensive cancer care.